2015
DOI: 10.1111/jcap.12108
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Practice in the Face of Complexity and Comorbidity: A Case Study of an Adolescent With Asperger's Syndrome, Anxiety, Depression, and Chronic Pain

Abstract: Routine outcome measurement demonstrated the effectiveness of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“… 40 Moreover, psychiatric disorders, in particular, anxiety and depression, are common in pediatric chronic pain, 41 , 42 and have been associated with elevated levels of functional impairments. 36 , 43 45 A few clinical reports, 46 49 a number of studies on abdominal pain, 20 , 50 a study on migraine, 51 and a recent study on neuropsychological function in chronic pain 40 have suggested that ASD and ADHD may be comorbid to pediatric chronic pain and that such comorbid neurodevelopmental conditions may go undetected. Importantly, however, the prevalence of these disorders, including clinically significant traits, in pediatric patients with chronic pain is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 40 Moreover, psychiatric disorders, in particular, anxiety and depression, are common in pediatric chronic pain, 41 , 42 and have been associated with elevated levels of functional impairments. 36 , 43 45 A few clinical reports, 46 49 a number of studies on abdominal pain, 20 , 50 a study on migraine, 51 and a recent study on neuropsychological function in chronic pain 40 have suggested that ASD and ADHD may be comorbid to pediatric chronic pain and that such comorbid neurodevelopmental conditions may go undetected. Importantly, however, the prevalence of these disorders, including clinically significant traits, in pediatric patients with chronic pain is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall prevalence of comorbid neurodevelopmental disorders, such as autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD), has not yet been established . A few cases described in the literature have indicated an overlap between chronic pain and ASD, including two on children who were under 12 years of age , and other studies have suggested that abdominal pain appears to be common and persistent among children with ASD . Furthermore, a 2017 study by Arruda et al reported that migraine, frequent migraine and ADHD were comorbid in the paediatric population.…”
Section: Introductionmentioning
confidence: 99%
“… 69 Previous cases in the literature showed an overlap between ASD and chronic pain, particularly among adolescents. 6 , 70 , 72 As previously mentioned, ASD has a strong genetic contribution, and advances of arrays and sequencing technologies have provided tools to elucidate both de novo single nucleotide variants and copy number variations and other genetic variants that contribute to approximately 10% to 40% of cases. 49 , 73–75 Sodium channels in ASD research have gained significant traction, with SCN2A , a gene that encodes a voltage-gated sodium channel subtype 2 alpha protein (Na v 1.2), becoming a front runner due to the sheer amount of de novo single nucleotide variants that occur in patients.…”
Section: The Autism Spectrum Disorder Risk Gene Scn9a and Pain Comorbiditiesmentioning
confidence: 99%